2016
DOI: 10.1007/s00223-016-0149-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Fracture Resistance of Bone with the Progression of Type 2 Diabetes in the ZDSD Rat

Abstract: Individuals with type 2 diabetes (T2D) have a higher fracture risk compared to non-diabetics, even though their areal bone mineral density is normal to high. Identifying the mechanisms whereby diabetes lower fracture resistance requires well-characterized rodent models of diabetic bone disease. Toward that end, we hypothesized that the bone toughness, more so than bone strength, decreases with the duration of diabetes in ZDSD rats. Bones were harvested from male CD(SD) control rats and male ZDSD rats at 16-wks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
68
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 41 publications
8
68
0
Order By: Relevance
“…In diabetes, where glucose levels are elevated, AGEs are deposited in many tissues, including bone . AGEs are associated with increased bone fragility in diabetes; thus, by lowering glucose levels, insulin may help to decrease accumulation of AGEs in bone . Nevertheless, in vivo evidence also suggests that insulin has a direct effect on bone formation and osteogenesis, irrespective of its effect on glucose metabolism.…”
Section: Drugs and Bonementioning
confidence: 99%
See 1 more Smart Citation
“…In diabetes, where glucose levels are elevated, AGEs are deposited in many tissues, including bone . AGEs are associated with increased bone fragility in diabetes; thus, by lowering glucose levels, insulin may help to decrease accumulation of AGEs in bone . Nevertheless, in vivo evidence also suggests that insulin has a direct effect on bone formation and osteogenesis, irrespective of its effect on glucose metabolism.…”
Section: Drugs and Bonementioning
confidence: 99%
“…74 AGEs are associated with increased bone fragility in diabetes; thus, by lowering glucose levels, insulin may help to decrease accumulation of AGEs in bone. 75,76 Nevertheless, in vivo evidence also suggests that insulin has a direct effect on bone formation and osteogenesis, irrespective of its effect on glucose metabolism. For instance, several studies in mice have shown that impaired insulin signaling, via knock-down of the insulin receptor specifically in osteoblast progenitors and mature osteoblasts, results in impaired bone formation, abnormal trabecular architecture, smaller cortices, and increased fragility, dependent on the developmental stage in which the insulin receptor was eliminated and in a sex-specific manner.…”
Section: Skeletal Effects: In Vivomentioning
confidence: 99%
“…AGEs can also inhibit the phenotypic expression of osteoblasts, interfere with osteoclast differentiation, and stimulate secretion of catabolic and proinflammatory factors . Accordingly, increased AGE accumulation with diabetes may underlie the impairments in cortical geometry and trabecular microarchitecture that have been reported in rodent models . In humans, cortical porosity is significantly higher at the distal radius and distal tibia in some cohorts with T2D, including cohorts with a fracture .…”
Section: Introductionmentioning
confidence: 99%
“…There are reports of greater concentrations of tissue AGEs (35) and greater mean calcium content in bone from people with T2DM compared with non-DM controls (36) ; however, rodent models of T2DM provide the bulk of evidence that T2DM alters tissue material properties. Multiple rodent models of T2DM report increased mineral content (assessed by mineral:matrix ratio) in Zucker diabetic Sprague-Dawley (ZDSD) rats (37,38) and KK-Ay mice compared with controls. (39) The same studies report no differences in concentrations of mature enzymatic crosslinks (pyridinoline and deoxypyridinoline) or in the AGE pentosidine (37)(38)(39) ; however, the collagen maturity (ratio of mature to immature enzymatic crosslinks) of the KK-Ay mice was increased compared with controls.…”
mentioning
confidence: 99%
“…Multiple rodent models of T2DM report increased mineral content (assessed by mineral:matrix ratio) in Zucker diabetic Sprague-Dawley (ZDSD) rats (37,38) and KK-Ay mice compared with controls. (39) The same studies report no differences in concentrations of mature enzymatic crosslinks (pyridinoline and deoxypyridinoline) or in the AGE pentosidine (37)(38)(39) ; however, the collagen maturity (ratio of mature to immature enzymatic crosslinks) of the KK-Ay mice was increased compared with controls. (39) In contrast, a study of WBN/Kob rats found a decrease in concentration of enzymatic crosslinks with a simultaneous increase in pentosidine concentration, (19) which suggests phenotype-specific changes in tissue material properties with T2DM.…”
mentioning
confidence: 99%